Protocols for Bio-Inspired Resource Discovery and Erasure Coded Replication in P2P Networks - Thampi, Sabu M.; SekaranK, Chandra (INFOCOMP Journal of Computer Science, 2010)
Efficient resource discovery and availability improvement are very important issues in unstructured P2P networks. In this paper, a bio-inspired resource discovery scheme inspired by the principle of elephants migration is proposed. A replication scheme based on Q-learning and erasure codes is also introduced. Simulation results show that the proposed schemes significantly increases query success rate and availability, and reduces the network traffic as the resources are effectively distributed to well-performing nodes